TOPOI DISCOURSES OF HIGHER EDUCATION - REFLECTIONS ON EMPIRICAL RESEARCH - Anna Kokocińska (Society Register)
The text serves as an attempt to summarise the analysis of public discourse which is a part of the research project which considered value of higher academic education in collective consciousness in Polish society. In the analysis of the collected empirical material, methodological directives of qualitative discourse analysis were applied. Main problem presented in the article are topoi that occur both in social and media discourse. It tries to answer the questions why are some ways of speaking about higher education more valid and sustainable than others and what are consequences of such an “use of language” for academic and non-academic worlds.